A factor decomposition analysis of transportation energy consumption and related policy implications. (March 2015) - Jiang, Jian
Abstract This paper introduces a method of factor decomposition analysis for analyzing the importance of the factors that affect the volume of transportation energy consumption. In choosing the influencing factors from the many possibilities, the paper introduces an indicator analysis to evaluate and select the most important affecting factors. Based on the decomposition results, the paper helps interpret the underlying causes of transportation energy consumption. At the same time, the paper also suggests corresponding policy implications for the improvement of transportation energy efficiency.